Pengaruh Kemampuan Menghafal al-Qur’anTerhadap Konsentrasi Belajar Siswa Madrasah Ibtidaiyah Muhammadiyah 6 Ponorogo - Choirunnisa, Rizky; Katni; Laksana, Sigit Dwi (Jurnal Pendidikan Nusantara, 2022)
Education is important for human existence because it broadens intellectual and spiritual perspectives. Education is very important not only for physical growth and development or human body, but also for spiritual growth and development. Education must start from a young age, because it can be used as a way of life until one reaches old age. The purpose of this study was to determine the effect of the students' ability to memorize the Qur'an at MI Muhammadiyah 6 Ponorogo on students' learning concentration. The research method used is quantitative, with a population of 96 students and a sample of 30 students who apply the memorization of the Qur'an. Data collection is done by using the technique of distributing questionnaires and documentation. The data were then analyzed using Descriptive Statistics and Prerequisite Analysis. The results showed that there was a positive and significant influence between the ability to memorize the Qur'an and the learning concentration of grade IV, V and VI students at MI Muhammadiyah 6 Ponorogo. This can be seen from the constant value of 16.987 and the regression coefficient value of the memorization ability of 0.755. With the regression equation, namely Y = 16.987 + 0.755X, it is known that the coefficient of determination of 34.6% is determined by the ability to memorize the Qur'an.